ANALYSIS OF CALCULATION OF PRODUCTION’S COST BY USING JOB ORDER COSTING METHOD AT UD. SIDO MAKMUR - Karina Utami Anastuti (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2022)
UD Sido Makmur is a business engaged in snack food services in the form of taro chips UD Sido Makmur was established in 2018 and until this year has 23 employees with salary payments every day. This study was conducted to evaluate the role of the Job Order Costing Method in determining the company's cost of goods manufactured. The cost of production must be determined accurately so that the company does not suffer losses. Companies must be able to accumulate production costs, both raw material costs, direct labor costs, and factory overhead costs. This research is a type of descriptive qualitative research where this study looks at the effectiveness of the extent to which the application of the Job Order Costing Method in determining the Cost of Production at UD Sido Makmur. From the results of the research and discussion above, the writer concludes that the method of imposing Factory Overhead Costs by UD Sido Makmur is not appropriate.